An Analysis of the Factors Contributing to Stress in Public and Private Sector Students of Pakistan - Noureen Kazim; Mamoona Ismail Loona; Minah Majid Javed; Kainat Zia (Research Journal of Psychology, 2025)
This study aimed at assessing academic stress sources among students from private and government institutions. The sample consisted of 300 participants from schools, colleges, and universities throughout both sectors. The study aimed to investigate the impact of academic stress on adolescents. Another purpose was to assess the researched variable concerning demographics (gender and institutions). A standardized instrument was employed; the Educational Stress Scale for Adolescents, developed by Sun, Dunne, Hou, and Xu (2010), consists of 16 items with a 5-point scale. This novel instrument for measuring academic stress can assess the multiple aspects of educational stress, including study pressure, grade anxiety, despondency, self-expectation, and workload. The Cronbach's alpha for the complete 16-item ESSA scale was .81, signifying strong internal consistency. T-tests and ANOVA were conducted on the data using SPSS. T-test analysis revealed a significant difference between students from both sectors for the analyzed variable. ANOVA indicates a substantial difference among pupils at the school, college, and university levels.